PEMBERDAYAAN KADER POSYANDU DAN IBU BALITA DALAM PROGRAM PEMBERIAN MAKANAN TAMBAHAN (PMT) DI POSYANDU DENGAN PENDEKATAN ASSET BASED COMMUNITY DEVELOPMENT (ABCD) - Tati Nuryati; Handayani, Handayani; Mellynia Kencana Dewi; Tasya Erindah Hidayat; Dimas Prapanca; Harleyna Surya; Zunaedi Salam; Maspuri Sahid (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Child nutrition problems are not only problems regarding the intake provided. Child nutrition problems in the community can occur due to several factors such as the lack of role of health workers, parental behavior (mothers), clean and healthy living behavior (PHBS) of the family, and risks and natural geographical conditions. Jayasakti Village, Muara Gembong District is a village located on the coast, this village still has child nutrition problems such as nutritional status not increasing, underweight, and stunting. The Jayasakti Village community also has other factors that can contribute to child nutrition problems such as difficult access to clean water for drinking and hygiene sanitation, the economic status of the head of the family who are mostly fishermen, and insecurity of access to food. Efforts to Provide Additional Food (PMT) have been carried out by the health center and the local village government as an effort to eradicate child nutrition problems. In its implementation, of course, various evaluations are needed so that the next PMT program can run better. This community service activity focuses on empowering cadres and parents of toddlers in implementing the PMT program in Jayasakti Village, the approach model used is Asset Based Community Development (ABCD), where this approach has a flow of activities that are suitable for application in the community service process in Jayasakti Village. The activity process involved 5 posyandu cadres and 22 parents of toddlers, and a series of activities carried out included Pre Test and Post Test, Forum Group Discussion, providing material on PMT from local food ingredients, educational games one table one goal, exploring aspirations, and signing a joint commitment to make PMT a success in the future. Some of the outputs obtained from this community service activity include the target of the activity to find out the potential assets that can be improved in the implementation of PMT, increasing knowledge measured through pre-test and post-test scores, aspirations and hopes of cadres and parents of toddlers regarding the implementation of PMT, and a joint commitment to make PMT a success in the future